2005
DOI: 10.4161/cc.4.4.1600
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Reovirus Oncolysis and Ras Signaling

Abstract: Reovirus is a benign virus with innate oncolytic activity and is a potential novel therapeutic for a number of cancers. Reovirus can replicate in, and induce death of cancerous cells having an activated Ras pathway. Ras activation leads to the inactivation of cellular antiviral mechanisms, specifically removing the translation block on reovirus transcripts. This review outlines recent progress towards elucidating the molecular connection between the Ras-signaling pathway and reovirus replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…8,9,44 The detailed relationship between the cell's Ras status and the various consequences of infection has not been fully elucidated yet. 5,44 While our data suggests components of the Ras/ RalGEF/p38 pathway 6 (particularly p38 and in some cell lines PI3K, but not MEK 1/2) are implicated in the reovirus-induced killing of melanoma (Figure 4), for clinical application the key findings of this study are the sensitivity of melanoma (both cell lines and primary tumours) to reovirus killing and replication, together with the relative resistance of Melan-A normal melanocytes. Sequencing to date of our lines has shown that they are all mutant in the Ras/BRAF pathway (as expected for melanomas 45 ), while Melan-A is normal.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…8,9,44 The detailed relationship between the cell's Ras status and the various consequences of infection has not been fully elucidated yet. 5,44 While our data suggests components of the Ras/ RalGEF/p38 pathway 6 (particularly p38 and in some cell lines PI3K, but not MEK 1/2) are implicated in the reovirus-induced killing of melanoma (Figure 4), for clinical application the key findings of this study are the sensitivity of melanoma (both cell lines and primary tumours) to reovirus killing and replication, together with the relative resistance of Melan-A normal melanocytes. Sequencing to date of our lines has shown that they are all mutant in the Ras/BRAF pathway (as expected for melanomas 45 ), while Melan-A is normal.…”
Section: Discussionmentioning
confidence: 97%
“…Since permissive reovirus replication is also a feature of cells with defects in pathways lying up or downstream of the Ras proteins themselves, this implicates a significant proportion of human tumours as potentially susceptible to reoviral oncolysis. 4,5 More recent studies have suggested that the determinants of susceptibility to reovirus-induced cell death may be more complex than simple generic activation of the Ras signalling pathway. Norman et al 6 reported that the activity of the Ras/RalGEF/p38 pathway is the major determinant of susceptibility in transformed NIH 3T3 cells; other work has suggested that Ras activation status does not affect reovirus replication in C26 murine colorectal cancer cells, but does influence their sensitivity to reovirus-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…We are now conducting further studies to identify a binding protein against CUG2 to resolve this question. Moreover, as ERK activity has been reported not to be involved in reoviral replication, 2,28 we only need to focus on Src kinase. However, inhibition of Src kinase activity does not affect reoviral replication (Figure 3b).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies proposed a model in which mutations in Ras inhibit antiviral protein kinase R (PKR) signaling and activate other signal transduction pathways to promote viral protein synthesis and apoptosis in reovirus-infected transformed cells (76). More recent work from our laboratory and others revealed that efficient cell entry of reovirus particles into transformed cells is a major determinant of its oncolytic potential (2,47,71).…”
mentioning
confidence: 99%